A Qualitative Exploration of Palliative Care Experiences among Javanese Patients and Families - Ruhyana Ruhyana; Wantonoro Wantonoro (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Cultural aspects play a crucial role in providing nursing care, particularly for patients and families with terminal or chronic illnesses undergoing palliative care. Understanding patients' and families' cultural aspects is essential to provide empathetic, effective, and culturally respectful palliative care. Method: This qualitative phenomenological study involved in-depth interviews with 10 participants (5 patients and 5 family members) selected through purposive sampling. Data were analyzed using Colaizzi's method. Result: Five main themes emerged reflecting the cultural perceptions of palliative care among Javanese patients and families: (1) Hope for recovery and a better life-serving as a spiritual and emotional anchor held by patients and families; (2) Family roles and responsibilities-encompassing caregiving duties, emotional support, and efforts to maintain family harmony and dignity; (3) Anxiety about the future-including concerns about dependency, financial burden, and the impact of loss, felt by both patients and families; (4) Life as a test and trial from God-a strong spiritual belief that illness is part of destiny, collectively accepted; (5) Surrender and acceptance (nrimo)-a characteristic Javanese attitude practiced by patients and families as a coping mechanism to find peace amidst uncertainty. Conclusion: Nrimo, sincere acceptance of illness as divine will, functions as an active, value-based coping mechanism that enhances resilience and spiritual well-being, differing from Western concepts of passive resignation. Healthcare professionals must validate nrimo as adaptive coping, not fatalism. Family-centered, indirect communication with early engagement of decision-makers is recommended. Spiritual care integration through religious leaders is essential for meaning-making.